2006
DOI: 10.1183/09031936.00077706
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-assisted transthoracic biopsy: fine-needle aspiration or cutting-needle biopsy?

Abstract: The present study compared the diagnostic yield of ultrasound-assisted cuttingneedle biopsy (CNB) and fine-needle aspiration biopsy (FNAB) in chest lesions.A physician performed ultrasound and FNAB with a 22-G spinal needle in all patients, directly followed by a 14-G CNB in patients without contraindication.A total of 155 consecutive lesions arising from the lung (74%), pleura (12%), mediastinum (11%) or chest wall (3%) in patients with a final diagnosis of lung carcinoma (74%), other malignant tumours (12%),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
58
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 9 publications
(11 reference statements)
7
58
0
4
Order By: Relevance
“…No pneumothoraces or major haemorrhage was caused, and only mild haemorrhage occurred in 4% of needle aspirations and 18.8% of biopsies. These findings are comparable to case series not limited to SVC syndrome [13,14].…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…No pneumothoraces or major haemorrhage was caused, and only mild haemorrhage occurred in 4% of needle aspirations and 18.8% of biopsies. These findings are comparable to case series not limited to SVC syndrome [13,14].…”
Section: Discussionsupporting
confidence: 76%
“…Numerous subsequent studies firmly established transthoracic mediastinal FNA and CNB as investigations with a diagnostic sensitivity ranging 80-90% [19][20][21][22] and as feasible alternatives to mediastinoscopy or diagnostic thoracotomy [23,24]. The present authors previously reported a combined diagnostic yield for US-assisted TTFNA and CNB of 89% in 155 consecutive patients with mass lesions that abutted the chest wall [14]. In that study, TTFNA had a significantly higher sensitivity than CNB in diagnosing bronchogenic carcinoma (95 versus 81%; p50.006), but CNB was superior in noncarcinomatous tumours and in benign lesions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations